“Eating” Cancer cells by blocking CD47 signaling: Cancer therapy by targeting the innate immune checkpoint - Yi-Rong Xiang (Cancer Translational Medicine, 2017)
Differing from the adaptive immune checkpoint mediated by programmed cell death-1 (PD-1) PD-1-ligand or CTLA-4, the CD47 and signal regulatory protein α (SIRPα) axis is emerging as a novel innate immune checkpoint of the immune cells of myeloid lineage. A balance should be established between the dual signals, the “Don't eat me signal” of CD47-SIRPα and the “Eat me signal” of calreticulin/low-density lipoprotein receptor-related protein. The enhanced expression of CD47 molecule has been found in many cancer tissues, including malignant blood tumors (acute myeloid leukemia) and solid tumors. A therapeutic value could be achieved by counteracting the expression of CD47 in cancer cells. In the recent years, great progress has been made to develop anticancer therapies by targeting CD47 (e.g., anti-CD47 antibody), in various types of cancer. However, there are a few challenges, like “antigen sink” in the clinical translation of CD47-mediated anticancer therapies, the attention to which is crucial.